L’histoire de la Pologne revisitée ou le jeu de l’implicite et de l’explicite dans la traduction française de Jak zawsze de Zygmunt Miłoszewski - Warmuzińska-Rogóż, Joanna (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The present article analyzes the French translation of Zygmunt Miłoszewski’snovel Jak zawsze (As usual) into French (translation: Kamil Barbarski, title: Te souviendras-tude demain?) and focuses particularly on the play between implicit and explicit elements relatedto the history and culture of Poland. The protagonists of the novel travel back in timefifty years to Poland, where it occurs that history unfolded completely differently than inreality. They have the opportunity to relive their lives in a different world, but it occursthat although their private lives will turn out differently, the history of Poland will end asusual. Miłoszewski uses stereotypes and allusions which, without explication in translation,will be incomprehensible or will lose their raison d’être. The author analyzes the translator’sstrategies and the ability to understand the text by the recipient of the translation.